Subjective Evaluation of Haptic Feedback Technologies for Interactive Multimedia - Silva, Bruno (2020)
Current trends in the development of remote control devices for user interaction with multimedia equipment and applications are increasingly advancing the traditional keypad-based technologies, in order to improve the functionality of remote control devices and also to enhance the user experience. Haptic feedback allows the user to have a similar sensation to that provided by conventional buttons, with the advantage of a much greater flexibility, including dynamic choice of mechanical effects capable of discriminating between different functions. However, selection of haptic feedback effects that are capable of enhancing the user experience remains a great challenge for engineers and product designers. This work is a contribution towards this goal by presenting a usability study of two technologies (eccentric rotating mass and linear resonant actuator) capable of providing different haptic feedback effects in remote control devices. A subjective evaluation study was carried out to obtain subjective scores for a significant number of haptic feedback effects. The number of preferred actuators of each type and whether haptic feedback is suitable in remote control devices for interactive multimedia, were also evaluated. The results of this study show that most users prefer an interface with haptic feedback and different scores were obtained for different haptic feedback effects, according to the characteristics and number of the actuators.